2015
DOI: 10.1007/s11947-015-1577-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Postharvest Quality and Storability of Jamun Fruit (Syzygium cumini L. var. Paras) by Zein Coating Enriched with Antioxidants

Abstract: Jamun (Syzygium cumin L.) is a minor indigenous underexploited and perishable fruit of India. Keeping its perishability in mind, the present study is aimed to evaluate the effectiveness of zein-based coatings enriched with cystein (0.2 %), ascorbic acid (0.2 %), and jamun leaves extract (JLE) (0.2 %) and to evaluate their interactive effects on shelf life and quality of fresh jamun fruits during storage at 10 ± 2°C for 2 weeks. The results of the present study demonstrated that during storage, uncoated fruit h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 56 publications
3
16
2
1
Order By: Relevance
“…However, mango fruit treated with chitosan reduced the activities of PG and PME enzyme in this study. These results are in line with previous reports, where edible coatings decreased the activities of pectolytic enzyme in pear and jamun during storage (Zhou et al, 2011;Baraiya et al, 2015). Chitosan coating positively inhibited the activities of PG and PME enzyme.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…However, mango fruit treated with chitosan reduced the activities of PG and PME enzyme in this study. These results are in line with previous reports, where edible coatings decreased the activities of pectolytic enzyme in pear and jamun during storage (Zhou et al, 2011;Baraiya et al, 2015). Chitosan coating positively inhibited the activities of PG and PME enzyme.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 93%
“…PME disintegrates the methyl and the carboxylic groups of the pectin and breaks the ester bonds, while PG acts on pectic acid chains and break the glycoside bonds between the galacturonic acid subunits (Brummell and Harpster, 2001). It has been observed that the cell wall degrading enzyme increased during ripening in mango (Razzaq et al, 2014), papaya (Madani et al, 2014) and Jamun (Baraiya et al, 2015). However, mango fruit treated with chitosan reduced the activities of PG and PME enzyme in this study.…”
Section: Journal Of Agricultural Studiescontrasting
confidence: 54%
“…In recent years, the use of edible coatings, in particular, polysaccharide-based coatings (starch, chitosan, xanthan gum, pectin, cellulose derivatives, and alginate), has shown great potential to delay fruit quality deterioration during cold storage due to their potential to reduce respiration rates and create a gas barrier on the fruit surface [ 10 , 11 , 12 , 13 ]. In addition, coatings can be supplemented with food compatible (and ideally natural) antioxidants to delay and reduce oxidative-related disorders [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treated root samples varied in their delay in phenol reduction and this may have been due to the different efficiencies of the coating solutions to delay PPD and oxygen depletion which caused enzyme inactivation (Salcedo & Siritunga, 2011). There was also notable delay in the browning of the coated cassava roots which may have been due to the inhibition of oxygen penetration by the coating solution as was reported by Baraiya et al (2015).…”
Section: Total Phenolic Contentmentioning
confidence: 80%
“…Coatings are a type of films directly applied on the food product surface. The application of edible coatings can improve the physical features of food products, reduce clustering of food particles and improve visual features on the product surface (Baraiya, Rao,& Thakkar, 2015). Many factors determine the success of edible coatings in improving quality and extending shelf-life of foods.…”
Section: Introductionmentioning
confidence: 99%